Societal Pressures Shaping Professional Identity and Motivation among Indonesian EFL Teachers' Experiences - Nonny Basalama; Haris Danial (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The professional identity and motivation of English as Foreign Language (EFL) teachers are shaped not only by pedagogical experiences but also by the broader social and economic contexts in which they work. In Indonesia, limited teacher remuneration and culturally embedded gender expectations continue to influence teachers’ professional engagement; however, the interaction between these factors remains underexplored in EFL research. This study aims to examine how economic constraints and gender expectations influence the professional identity and motivation of Indonesian EFL teachers. A qualitative narrative inquiry was employed involving twenty secondary school EFL teachers from Indonesia. Data were collected through semi-structured, in-depth interviews and analyzed using thematic analysis to identify recurring patterns across participants’ experiences. The findings reveal that inadequate remuneration negatively affects teachers’ motivation, professional development, instructional creativity, and participation in continuous learning. Nevertheless, teachers with a strong sense of professional vocation demonstrated sustained commitment despite financial challenges. The study also found that gender expectations significantly shaped teachers’ career decisions and professional identity. Male teachers commonly undertook additional employment to fulfill their responsibilities as family breadwinners, whereas married female teachers prioritized domestic and caregiving responsibilities, resulting in different forms of professional engagement. These findings indicate that professional identity is dynamically negotiated through the interaction between personal agency and contextual pressures rather than being determined solely by individual beliefs or professional competence. The study highlights the importance of improving teacher welfare and developing context-sensitive educational policies that recognize the influence of economic conditions and sociocultural expectations on teacher motivation, professional identity, and long-term career sustainability.